Storynomic as Marketing Strategy of Telaga Sarangan Magetan - Irma Kusuma Dewi; Dinda Rakhma Fitriani (CV. Inara, 2021)
The purpose of this research is to find out how the storynomics tourism approach can be used for marketing Sarangan Lake tourism. Sarangan Lake has a strong legend in the Sarangan community and even the wider community so that it can attract tourists to visit, the challenge is how this message can be conveyed to tourists not only conveying mythical values ​​but also packaged in other forms so as to provide educational value to every visitor. The research method used is descriptive qualitative. The purpose of this research is to find out how story economics tourism methods can be used to market Sarangan Lake tourism. Sarangan Lake has a strong legend in the Sarangan community and the wider community, so it can attract tourists to visit. The challenge is how to convey this information to tourists, not only to convey the value of mythology, but also to package in other forms, thereby Provide educational value for every visitor. The research method used is descriptive qualitative research. Data is collected through observations, records and interviews. The results show that the story economics method can be used as an effective strategy for marketing the Sarangan Lake destination and can indirectly increase the interest in visiting the place.